2006
DOI: 10.1152/ajpheart.01215.2005
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte adherence inhibits adenosine-dependent venular control of arteriolar diameter and nitric oxide

Abstract: Kim, Min-ho, and Norman R. Harris. Leukocyte adherence inhibits adenosine-dependent venular control of arteriolar diameter and nitric oxide. Am J Physiol Heart Circ Physiol 291: H724 -H731, 2006. First published March 31, 2006 doi:10.1152/ajpheart.01215.2005.-Venular control of arteriolar perfusion has been the focus of several investigations in recent years. This study investigated 1) whether endogenous adenosine helps control venule-dependent arteriolar dilation and 2) whether venular leukocyte adherence li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Hein et al claimed that this localized flow control is critical for the modulation of retinal vascular tone due to the absence of autonomic innervation in the retinal circulation [ 8 , 19 ]. Whether this form of retinal arteriolar flow control is venule dependent, as is the case for adenosine in mesenteric tissue [ 25 ], and for arachidonic acid metabolites in stimulated cremaster tissue [ 15 ], has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Hein et al claimed that this localized flow control is critical for the modulation of retinal vascular tone due to the absence of autonomic innervation in the retinal circulation [ 8 , 19 ]. Whether this form of retinal arteriolar flow control is venule dependent, as is the case for adenosine in mesenteric tissue [ 25 ], and for arachidonic acid metabolites in stimulated cremaster tissue [ 15 ], has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…NO, prostaglandins, and adenosine have been implicated as mediators of venule-induced arteriolar dilation. Adenosine-and venule-dependent dilation of paired arterioles may be mediated by NO and inhibited by venular leukocyte adherence [27]. Activated platelets can release the potent vasoconstrictor thromboxane, and platelet adherence in venules was associated with the constriction of closely paired arterioles in a model of dextran sodium sulfate-induced inflammation [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intravital microscopy has also been used to test novel prophylactic and therapeutic approaches that aim to prevent or attenuate manifestations of sepsis-associated microvascular disorders and cellular dysfunctions. In the mesentery, microcirculatory observations have focused on capillary obstruction, capillary or arteriolar density, microvessel reactivity and leukocyte-endothelial interactions in post-capillary venules (Harris, 2006;Kim & Harris, 2006;Nakagawa et al, 2006Nakagawa et al, , 2007Schimidt et al, 1997;Smalley et al, 2000;Walther et al, 2004;Woodman et al, 2000). A representative photomicrograph of rat mesenteric microcirculation is shown in Figure 3.…”
Section: Intravital Microscopy In the Assessment Of Microcirculationmentioning
confidence: 99%
“…Microcirculatory dysfunctions, as seen in humans (De Backer & Dubois, 2001;De Backer et al, 2002;Groner et al, 1999;Trzeciak et al, 2007), have been shown to occur in most experimental models of sepsis (Baveja et al, 2002;Kamoun et al, 2005;Kim & Harris, 2006;Kubo et al, 1999;Nakagawa et al, 2006Nakagawa et al, , 2007Nakajima et al, 2001;Schimidt et al, 1997;Smalley et al, 2000;Waisman et al, 2006;Walther et al, 2004;Woodman et al, 2000). Endotoxin infusion is a widely used experimental model (Kim & Harris, 2006;Schimidt et al, 1997;Smalley et al, 2000;Nakajima et al, 2001).…”
Section: Intravital Microscopy In the Assessment Of Microcirculationmentioning
confidence: 99%
See 1 more Smart Citation